Hydrogen sulfide in ageing, longevity and disease. Issue 19 (15th October 2021) - Wilkie, Stephen E.; Borland, Gillian; Carter, Roderick N.; Morton, Nicholas M.; Selman, Colin
Abstract : Hydrogen sulfide (H2 S) modulates many biological processes, including ageing. Initially considered a hazardous toxic gas, it is now recognised that H2 S is produced endogenously across taxa and is a key mediator of processes that promote longevity and improve late-life health. In this review, we consider the key developments in our understanding of this gaseous signalling molecule in the context of health and disease, discuss potential mechanisms through which H2 S can influence processes central to ageing and highlight the emergence of novel H2 S-based therapeutics. We also consider the major challenges that may potentially hinder the development of such therapies.